Odpowiedź :
3x-12=2x+4
3x-2x=4+12
x=16
4x-12>6x+12
4x-6x>12+12
-2x>24 /(-2)
x<12
3x-2x=4+12
x=16
4x-12>6x+12
4x-6x>12+12
-2x>24 /(-2)
x<12
a) 3x-12=2x+4
3x-2x=4+12
X=16
b)4x-12>6x+12
4x-6x>12+12
-2x>24 /(-2)
x<12
c)(x-2)²-3(x+1)=(x+2)(x-2)-2
x²-4x+4-3x-3=x²-4-2
x²- x²-4x-3x= -6+3-4
-7x= -7/ : -7
X= 1
d)(x-4)² +x = x² -5
x²-8x+16+x = x²-5
x²- x²-8x+x= -5-16
-7x= -21/ :-7
X=3
3x-2x=4+12
X=16
b)4x-12>6x+12
4x-6x>12+12
-2x>24 /(-2)
x<12
c)(x-2)²-3(x+1)=(x+2)(x-2)-2
x²-4x+4-3x-3=x²-4-2
x²- x²-4x-3x= -6+3-4
-7x= -7/ : -7
X= 1
d)(x-4)² +x = x² -5
x²-8x+16+x = x²-5
x²- x²-8x+x= -5-16
-7x= -21/ :-7
X=3